APPLICATION OF RANDOMIZED RESPONSE TECHNIQUE ON A SURVEY OF DRUG ABUSE AMONG UNDERGRADUATE STUDENTS IN NIGERIA - Okoduwa, H. J.; Aladeniyi, O. B.; Famose, O. A. (FUDMA Journal of Sciences, 2024)
This study investigated the efficacy of the Randomized Response Technique (RRT) in addressing the challenge of underreporting in surveys related to drug abuse in Nigerian Universities. Recognizing the inherent social stigma and confidentially concerns associated with self-disclosure, the RRT is employed as a methodological strategy to elicit more accurate and truthful responses. The research assessed the feasibility and effectiveness of the RRT in uncovering the prevalence and patterns of drug abuse among survey undergraduate students of the Federal University of Technology, Akure, Nigeria. Estimate-adjusted proportion was used to ascertain the drug abuse prevalence while the chi-square test proved to be the most suitable statistic for comparing the relationship between the variables. Confidence interval was used to determine the range in which the true prevalence lied. It was deduced that the proportion of drug abuse among undergraduates using the RRT is 0.3907 which amounts to 39% of the population. Additionally, 64% believed that peer pressure proved to be a strong contributing factor to drug abuse among this population group. While there was no significant relationship between drug abuse and the students’ allowance. Consequently, efforts that aimed at empowering undergraduates in the universities or higher schools of learning against drug abuse should be vigorously pursued by the government and other stakeholders to eradicate or reduce this menace called drug abuse.